2018
DOI: 10.1016/j.omtn.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The Antibiotic-free pFAR4 Vector Paired with the Sleeping Beauty Transposon System Mediates Efficient Transgene Delivery in Human Cells

Abstract: The anti-angiogenic and neurogenic pigment epithelium-derived factor (PEDF) demonstrated a potency to control choroidal neovascularization in age-related macular degeneration (AMD) patients. The goal of the present study was the development of an efficient and safe technique to integrate, ex vivo, the PEDF gene into retinal pigment epithelial (RPE) cells for later transplantation to the subretinal space of AMD patients to allow continuous PEDF secretion in the vicinity of the affected macula. Because successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Importantly, alongside the elevated PEDF level, a decrease of MMP-2 expression is according to the observed antiangiogenic environment following tIPE and tRPE cell therapy. These results are consistent with our previous pilot studies showing safety, effectiveness at a higher single dose, and survival of PEDF-expressing cells transplanted in the rat subretinal space 31 , 49 , 53, 54, 55, 56, 57, 58…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, alongside the elevated PEDF level, a decrease of MMP-2 expression is according to the observed antiangiogenic environment following tIPE and tRPE cell therapy. These results are consistent with our previous pilot studies showing safety, effectiveness at a higher single dose, and survival of PEDF-expressing cells transplanted in the rat subretinal space 31 , 49 , 53, 54, 55, 56, 57, 58…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, there is a great demand for developing a treatment that allows for the maintenance of high PEDF level for an extended period of time. In Europe, a phase Ib/IIa ex vivo gene therapy clinical trial for long-term expression of PEDF in IPE cells by combining pFAR4 miniplasmid and SB transposon technologies is planned and has been submitted for approval to Swiss regulatory authorities Swissmedic 31 , 49 , 55 (https://www.targetamd.eu/), with all preclinical tests completed 82 . Our approach is based on the use of RPE and IPE cells because they show similar characteristics and many functions in common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of the FBXW5 (S1) and FBXW5 (S3) are highly conserved between mouse and human on the basis of sequences alignment. After 8 weeks of HFHC diet feeding, we delivered a hemagglutinin (HA)‐tagged pT3 plasmid carrying human FBXW5 (S1) or FBXW5 (S3) (pT3‐FBXW5(S1 or S3)‐HA) and the SB100X transposase plasmid into mice liver followed by another 8 weeks of HFHC diet feeding (Supporting Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) can result in significantly decreased vision, subsequently impacting a patient's independence with activities of daily living, social relationships, financial security, and general mental well-being. [1][2][3][4] A utility value study of MD found that patients with minor visual impairment would trade 11% of their remaining lifetime to restore their vision, while patients with severe impairment would trade 60%; highlighting the significant impact AMD can have on the individual. [5] An understanding of the concerns, experiences, and perspectives of patients with wet MD is critical in delivering patient-centered care and improving life quality over a long period.…”
Section: Introductionmentioning
confidence: 99%